2014
DOI: 10.1007/s11657-014-0185-0
|View full text |Cite
|
Sign up to set email alerts
|

The Tromsø Study: Fit Futures: a study of Norwegian adolescents’ lifestyle and bone health

Abstract: Summary Bone mass achievement predicts later fracture risk. This population-based study describes bone mineral density levels (BMD) and associated factors in Norwegian adolescents. Compared with international reference ranges, BMD levels appear higher and physical activity levels are positively associated with BMD.Purpose Norway has one of the highest reported incidences of osteoporotic fractures. Maximization of peak bone mass may prevent later fractures. This population-based study compared BMD levels of Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 42 publications
4
70
1
Order By: Relevance
“…The underlying mechanisms behind the effects of contraceptives are complex and data on length of use and dosage are lacking. Winter et al reported that late sexual maturation was associated with low aBMD levels in TFF1 [31]. The fact that proportions of sexual maturation categories in our study are comparable with other Norwegian youth cohorts [40] and that the association between late sexual maturation and increased odds for positive deviation in this longitudinal study is consistent suggest that this adverse effect levels out to some extent.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The underlying mechanisms behind the effects of contraceptives are complex and data on length of use and dosage are lacking. Winter et al reported that late sexual maturation was associated with low aBMD levels in TFF1 [31]. The fact that proportions of sexual maturation categories in our study are comparable with other Norwegian youth cohorts [40] and that the association between late sexual maturation and increased odds for positive deviation in this longitudinal study is consistent suggest that this adverse effect levels out to some extent.…”
Section: Discussionsupporting
confidence: 88%
“…PA seemed beneficial for TB aBMD, but we found no clear dose-response effect. This may indicate that participants reporting to be in the hard training and competition category at baseline were already at the tail of the z-score distribution as reported by Winther et al [31]. Sustained activity level during follow-up and preservation of high z-score could lead to classification into the reference group no change or downwards drift for these participants.…”
Section: Discussionmentioning
confidence: 65%
“…The Danish study included 119 versus 765 in ours. Furthermore, as bone mass acquisition varies in girls and boys during adolescence [21], our analyses were performed sex stratified in contrast to the study of Jensen et al…”
Section: Discussionmentioning
confidence: 99%
“…The invited cohort comprised 1117 adolescents and 1038 (508 girls and 530 boys) attended the survey (93%). The cohort characteristics have been described in detail previously [21,22]. The present investigation includes participants aged 15-18 years of age (n = 961).…”
Section: Study Population and Design: The Tromsø Study Fit Futuresmentioning
confidence: 99%
“…Students in upper secondary school from two municipalities in northern Norway (Tromsø and Balsfjord) were invited to participate in the population-based Tromsø Study youth survey, Fit Futures, which has been described in detail elsewhere [13,14]. …”
Section: Methodsmentioning
confidence: 99%